Groundnut cassava maize intercrop yields over three cycles of planted tree fallow/crop rotations on Ultisol in Southern Cameroon - Hauser, S. (2008)
Lack of crop yield response to planted tree fallow led to introducing a two-year fallow phase to determine if planted tree fallow can improve soil fertility and yields over a no-tree control. Three cycles of two years fallow followed by slash-and-burn land preparation and one year of groundnut /cassava/maize intercropping were conducted with Senna spectabilis, Flemingia macrophylla and Dactyladenia barteri as planted hedgerow fallows and a no-tree control on an Ultisol in southern Cameroon. The land had been continuously cropped to maize/cassava intercrop for 5 years previous to the first two-year fallow phase. Groundnut grain yields were unaffected by fallow system in 1998 and 2001 and the sum of the three cropping years. Maize grain yield was unaffected by fallow system in 1998. In 2001 and 2004 maize grain yield was highest in the S. spectabilis system. Total maize grain yield across the three cropping years was higher in the F. macrophylla and S. spectabilis systems than in the D. barteri system. Cassava root yields were in all years and the sum of the 3 years unaffected by fallow system. Cassava root (1998, 2001) and groundnut grain (2001) yields had significant spatial responses to the distance from hedgerows, with yield increases with increasing distance from hedgerows. Annual biomass production of hedgerow prunings during cropping phases ranged from zero (D. barteri) to 3.4 Mg ha–1 (S. spectabilis). During the growth of groundnut and maize, hedgerows produced < 1 Mg ha–1 in 1998, < 0.6 Mg ha–1 in 2001 and < 0.8 Mg ha–1 at any individual pruning. Combined relative crop yields over the three cycles were lower in planted fallow than in the no-tree control. The N export with groundnut and maize grain and cassava roots, as an indicator of crude protein production was lower in the planted hedgerow fallow systems than in no-tree control. The planted fallow hedgerow system appears unsuitable to improve crop yields because the nutrient supply from prunings is low due to their low biomass production. Yet on short distances, the spatial response of cassava and groundnut indicates competition between hedgerows and crops, which was most pronounced on cassava and groundnut in the S. spectabilis system. The crop combination appears incompatible as benefits realized by the maize were outweighed by losses in groundnut.